2018
DOI: 10.1111/ibi.12578
|View full text |Cite
|
Sign up to set email alerts
|

Mixed patterns of morphological adaptation to insularity in an aerial displaying bird, the Common Snipe Gallinago gallinago

Abstract: On islands, colonizing birds may evolve behavioural and morphological adaptations to the new environment, often resulting in changes in body size and reduction or even total loss of flight. These island populations have therefore been used to test hypotheses related to adaptations for flight. However, in certain species in which flight is used not only in foraging and migration but also in mating displays, disentangling the effects of natural and social selection is difficult. Thus, sedentary populations of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…In our analysis, this was true for both populations, and across populations, there was no difference in size in either females or males. In a previous work, Rodrigues et al (2018) found a similar case of a trait involved in social signalling not responding as predicted by insular biogeography theory: in the Azorean Common Snipe (Gallinago gallinago), wing shape did not change with loss of migratory behaviour, probably due to the use of flight displays in this species during the reproductive season.…”
Section: Discussionsupporting
confidence: 58%
“…In our analysis, this was true for both populations, and across populations, there was no difference in size in either females or males. In a previous work, Rodrigues et al (2018) found a similar case of a trait involved in social signalling not responding as predicted by insular biogeography theory: in the Azorean Common Snipe (Gallinago gallinago), wing shape did not change with loss of migratory behaviour, probably due to the use of flight displays in this species during the reproductive season.…”
Section: Discussionsupporting
confidence: 58%
“…thus social selection, on this trait (Rodrigues et al 2018). Species differences in skeleton and external measurements are small compared with those in plumage traits, suggesting that the latter diverged more rapidly.…”
Section: Discussionmentioning
confidence: 93%
“…However, a comparative study between migratory and sedentary Common Snipe found no differences in wing shape, suggesting a possible influence of display behaviour, and thus social selection, on this trait (Rodrigues et al . 2018).…”
Section: Discussionmentioning
confidence: 99%